Semiotic Analysis of the Changes of Ondel-ondel Costume Elements as a Betawi Cultural Negotiation - Mita Purbasari Wahidiyat; M. Dwi Marianto; M. Agus Burhan (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2022)
Recognized as one of Jakarta’s icons, the large pair of puppets known as ondel-ondel has undergone significant transformation since its origin centuries ago. Classically built in a fairly simple form, ondel-ondel presents itself in various ways at every performance. Now, ondel-ondel is increasingly found throughout Jakarta, having gone through numerous changes in its costume elements. Whereas it is usually meant to be shown as a couple, nowadays a single ondel-ondel can be found cruising alleys with a mere digital sound system as musical accompaniment. Once respected and feared for its looks, today it is belittled by its own people. Due to this phenomenon, this research aimed to answer the questions of who influenced this ideological change, which ruling elite encouraged their ideology, and what the ideology is. Interviews and direct observations produced stories and photographs, while literature and media studies provided a historical background. Roland Barthes’ semiotic connotations with a historical perspective were used to read the hidden concepts behind these signs, which connect the changes of the costume elements through the important events in Betawi society during the period of 1970–2020. The different interests of each party brought more conflict in their relations, which created a dynamic cultural negotiation. Based on the results, the terms for the ondel-ondel models were identified, specifically a personification model, Islamic model, and commercial model, each named after the historical events and ideology brought about by Jakarta’s ruling elites.